Accommodating Fun at Work Environment to Improve Employees Engagement - Nugroho, Cahyo Aji; Suryani, Erma (IPTEK Journal of Proceedings Series, 2020)
In companies’ work of world nowadays, employees’ psychological connection with their work has gained critical importance. In this context, companies not only must recruit the top talent, but must also inspire and enable employees to apply their full capabilities to their work by conditioning supportive working environment called fun at work. Grati Project, PT. Hutama Karya (Persero) holds a big project engaged in Combine Cycle Power Plant (CCPP). As a project accommodating many employees, the company realizes some internal and external factors that potentially create distraction and disharmony fostering disengagement and disrupting its flow. Anticipating this condition, Grati Poject, PT. Hutama Karya (Persero) creates some forms of workplace fun offer individual employee enjoyment which stimulates greater overall engagement with the team and company itself. However, this has not been confirmed because there is no research in this project discussing about the implementation of fun at work in order to increase employee involvement in Grati Project PT. Hutama Karya (Persero). This research descriptive explorative aims to evaluate the implementation of fun at work in Grati Project PT. Hutama Karya (Persero) in order to increase employee work engagement and identify the obstacles/ problems in it. This research also reveals the efforts/ strategies taken by the company to maintain employee work involvement by implementing fun at work program. Method of data collection in this research use preliminary survey and main survey through web-based questionnaire, interview and observation. Method of data analysis use descriptive explorative gained from Miles & Huberman interactive analysis which consist of: (1) Data Reduction, (2) Present Data, and (3) Taking and Testing Conclusion. Result of this research are implementation 4 (four) fun at work dimension (socializing at work, celebrating at work, personal freedoms, dan global fun at work) that its real make work environment become fun then automatically improve employee work involvement which consist of 3 (three) dimension of vigor, dedication and work absorption. Result of this research also indicate problem and effort to resolve in order to implementation fun at work to improve employee work involvement which consist of: a) technical factor, b) social external factor, c) financial factor, d) fast program schedule, e) employee discipline and integrity